Turning Malaysia off inter-faith strife - Malik, Maszlee (ISEAS Yusof Ishak Institute, Singapore, 2016)
Since 2008, Malaysia has witnessed a series of incidents, which though piecemeal and coincidental, threatens the very fabric of Malaysian multi-ethnic and multi-religious co-existence.